Investigational drugs to treat hemophilia. (3rd March 2020) - Franchini, Massimo; Marano, Giuseppe; Pati, Ilaria; Veropalumbo, Eva; Vaglio, Stefania; Pupella, Simonetta; Masiello, Francesca; Cruciani, Mario; Mengoli, Carlo; Liumbruno, Giancarlo Maria
ABSTRACT: Introduction: Hemophilia A and B are congenital bleeding disorders. The current standard management of patients with severe hemophilia is prophylaxis which is given intravenously two or three times weekly; however, this is associated with a significant burden on the quality of life of the patient. The main attempts to improve the management of hemophilia is hence through the development of a new generation of products with properties facilitating prophylaxis and/or a better control of bleeding. Areas covered: This review describes the preclinical and phase 1/2 studies investigating the innovative products for the management of hemophilia patients with or without coagulation factor inhibitors. Expert opinion: Numerous innovative therapeutics, including factor concentrates and non-clotting factor-based therapies with extended half-life, are under clinical investigation. Among replacement therapies for hemophilia A, the results from phase 1/2 studies indicate that the most interesting products are those bioengineered using XTEN fusion technology. The anti-tissue factor pathway inhibitor antibody concizumab is the most innovative and interesting agent among non-clotting factor products. If the results of ongoing trials confirm the preliminary positive results, these promising agents will provide further improvements in the management and quality of life of patients with hemophilia.